Driving forces for science and technology development: Vision from agriculturial sector - Hoa, Tran Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Science and technology (S&T), with large contributions to agricultural growths in recent time, is considered as breakthrough move in agricultural production. Even with exceptional growths during more than 30 years, Vietnam agriculture really did not develop as its potentials and advantages could make. The question is what to do to make S&T develop and produce more contributions to Vietnam agriculture. This paper shares some solutions of driving nature for S&T development in this sector. Code: 14051601